Early modern India: literatures and images, texts and languages - Burger, Maya; Cattoni, Nadia (CrossAsia-eBooks, 2019)
A selection of contributions presented at the 12th International Conference on Early Modern Literatures of North India
Keywords: Konferenzschrift; Geschichte; Bhakti-Dichtung; Miniatur; Literatur; Indien